Desarrollo de un modelo de determinación de cash-flows para un proyecto de energía eólica - Irene Clara Pisón Fernández; Félix Puime Guillén; Miguel Ángel Crespo Cibrán (Atlantic Review of Economics, 2015)
– In this paper, the problems linked to renewable wind power energy production are analyzed and a model to define the variables in which the wind power business plan relies on is proposed. The viability plan shows that the shareholder's cash flows obtained in this kind of projects make it possible to face future investments with adequate returns, pointing to the renewable energy sector, in particular wind power as a strategic one within the Spanish economy over the coming decades.
Keywords: Q4; Q42; G31; 330; cash-flow; rentabilidad; wind power; cash-flow; profitability